2007
DOI: 10.1248/bpb.30.708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tremella fuciformis on the Neurite Outgrowth of PC12h Cells and the Improvement of Memory in Rats

Abstract: The Heterobasidiae edible mushrooms are a subclass of Basidomycetes, and the the fruiting bodies of Tremella fuciformis (TF), namely White-jelly-fungus or Silver-ear, are very popular in China as a medicinal remedy with nutritive and tonic actions for treating debility and exhaustion. A variety of semi-purified polysaccharides have been isolated and characterized from the TF spore (designated as polysaccharide A and B) 1) and the fruiting bodies. 2,3) Considerable attention has recently been drawn to the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 55 publications
0
22
0
1
Order By: Relevance
“…Lysophosphatidylethanolamine from Grifola frondosa was found to induce activation of MAP kinase cascade in PC-12 cells and resulted in neuronal differentiation and suppression of serum deprivation-induced apoptosis [39]. Tremella fuciformis crude aqueous extract contains polysaccharides, including glycosaminoglycan, promoted neuritogenesis, peripheral nerve regeneration, and muscle reinnervation following a sciatic nerve lesion [4042]. Park et al reported that exo-polysaccharides from the culture broth of Hericium erinaceus were shown to enhance the growth and neuronal differentiation of rat pheochromocytoma cells (PC-12) [43].…”
Section: Resultsmentioning
confidence: 99%
“…Lysophosphatidylethanolamine from Grifola frondosa was found to induce activation of MAP kinase cascade in PC-12 cells and resulted in neuronal differentiation and suppression of serum deprivation-induced apoptosis [39]. Tremella fuciformis crude aqueous extract contains polysaccharides, including glycosaminoglycan, promoted neuritogenesis, peripheral nerve regeneration, and muscle reinnervation following a sciatic nerve lesion [4042]. Park et al reported that exo-polysaccharides from the culture broth of Hericium erinaceus were shown to enhance the growth and neuronal differentiation of rat pheochromocytoma cells (PC-12) [43].…”
Section: Resultsmentioning
confidence: 99%
“…11) In this study, mice were treated with zeatin via drinking water at various concentrations, of 0.002%, 0.004%, and 0.008% (w/v), for up to 21 d prior to Scop prescription. Scop, which is a competitive antagonist at the muscarinic acetylcholine receptor, causes memory deficits and decreased cholinergic activity during behavioral performance.…”
mentioning
confidence: 99%
“…fuciformis has gained wide popularity as an effective health food and has become one of the valuable mushrooms. To date, there are many reports regarding the culture condition of T. fuciformis spores, characterization of polysaccharides, and their biological activities produced from the extract of these spores [4,[6][7][8].…”
mentioning
confidence: 99%